Study of defects influence on chlorinated polyvinyl chloride pipes damage and analysis of their fracture - Fatima Gugouch; Meriem Meknassi; Mohamed Elghorba; Achraf Wahid; Houda Mouradi; Bouhsiss Hassan; Aziz Maziri (Fracture and Structural Integrity)
In several industrial applications, plastic, composites and ceramics replace a number of metallic structures such as copper, aluminum and steel. Most recently installed piping water and gas systems in the world are made of thermoplastic due to its advantages, for example, low cost, ease of fabrication and corrosion resistance. In this work, the chosen material is chlorinated polyvinyl chloride (CPVC); the best one used to transport cold and hot water beside simplicity of installation. Notwithstanding, the pipes in service are submitted to different loads, related to environmental, thermal and mechanical effects which procure to mechanisms of degradation. The aim of this article is to assess the effect of the defect on CPVC pipes, through a study of the defect criticality in the form of semi-elliptical, then the ability to predict defected pipes residual life. Therefore unexpected and sudden failure caused by pipes accelerated damage. Therefore, we performed burst tests on both pre-damaged CPVC pipes and virgin ones. To lead our work in this paper, interested in the damage modeling and the failure analysis of CPVC pipes, we adapted the model of unified theory static damage, originally developed in fatigue. We used burst pressure tests to identify the limits of three damage progression phases and, in turn, to calculate the critical life fraction at which these flaws become harmful. Furthermore, we identify the critical depth for the studied defect. These results and techniques enable industrialist s to anticipate this structures service life under these conditions after that set up a robust system of maintenance to ensure a reliable and safe functioning of the structure.